Analysis of Placental Arteriovenous Formation Reveals New Insights Into Embryos With Congenital Heart Defects - Kalisch-Smith, Jacinta I.; Morris, Emily C.; Strevens, Mary A. A.; Redpath, Andia N.; Klaourakis, Kostantinos; Szumska, Dorota; Outhwaite, Jennifer E.; Sun, Xin; Vieira, Joaquim Miguel; Smart, Nicola; De Val, Sarah; Riley, Paul R.; et al. (Frontiers in Genetics, 2022)
The placental vasculature provides the developing embryo with a circulation to deliver nutrients and dispose of waste products. However, in the mouse, the vascular components of the chorio-allantoic placenta have been largely unexplored due to a lack of well validated molecular markers. This is required to study how these blood vessels form in development, and how they are impacted by embryonic or maternal defects. Here we employed marker analysis to characterise the arterial/arteriole and venous/venule endothelial cells (ECs) during normal mouse placental development. We reveal that placental ECs are potentially unique compared with their embryonic counterparts. We assessed embryonic markers of arterial ECs, venous ECs and their capillary counterparts – arteriole and venule ECs. Major findings were that the arterial tree exclusively expressed Dll4, and venous vascular tree could be distinguished from the arterial tree by Endomucin (EMCN) expression levels. The relationship between the placenta and developing heart is particularly interesting. These two organs form at the same stages of embryogenesis and are well known to affect each other’s growth trajectories. However, although there are many mouse models of heart defects, these are not routinely assessed for placental defects. Using these new placental vascular markers, we reveal that mouse embryos from one model of heart defects, caused by maternal iron deficiency, also has defects in the formation of the placental arterial, but not the venous, vascular tree. Defects to the embryonic cardiovascular system can therefore have a significant impact on blood flow delivery and expansion of the placental arterial tree.